Antisense Repression of Both ADP-Glucose Pyrophosphorylase and Triose Phosphate Translocator Modifies Carbohydrate Partitioning in Potato Leaves. - Hattenbach, A. (1997)
Previous experiments have shown that carbohydrate partitioning in leaves of potato (Solanum tuberosum L.) plants can be modified by antisense repression of the triose phosphate translocator (TPT), favoring starch accumulation during the light period, or by leaf-specific antisense repression of ADP-glucose pyrophosphorylase (AGPase), reducing leaf starch content. These experiments showed that starch and sucrose synthesis can partially replace each other. To determine how leaf metabolism acclimates to an inhibition of both pathways, transgenic potato (S. tuberosum L. cv Desiree) plants, with a 30% reduction of the TPT achieved by antisense repression, were transformed with an antisense cDNA of the small subunit of AGPase, driven by the leaf-specific ST-LS1 promoter. These double-transformed plants were analyzed with respect to their carbohydrate metabolism, and starch accumulation was reduced in all lines of these plants. In one line with a 50% reduction of AGPase activity, the rate of CO2 assimilation was unaltered. In these plants the stromal level of triose phosphate was increased, enabling a high rate of triose phosphate export in spite of the reduction of the TPT protein by antisense repression. In a second line with a 95% reduction of AGPase activity, the amount of chlorophyll was significantly reduced as a consequence of the lowered triose phosphate utilization capacity.